Building South-North bridges on the information superhighway : towards a global agenda for collaborative research and action : report - Akhtar, Shahid (IDRC OttawaCA, 1995)
Seeks to establish priorities for research on the implications of information for the developing world. Identifies four areas where research can be carried out to support policy development and action. These areas cover the economics of information and communication resources, the infrastructure underlying telecommunications and information technology, the applications of communications networks and services and questions related to access to services and content.